Delineation of ADPRHL2 Variants: Report of Two New Patients with Review of the Literature - Öz Yıldız, Sibel; Yalnızoğlu, Dilek; Şimsek Kiper, Pelin Özlem; Göçmen, Rahşan; Soğukpınar, Merve; Utine, Gülen Eda; Haliloğlu, Göknur (Neuropediatrics, 2024)
ADPRHL2 is involved in posttranslational modification and is known to have a role in physiological functions such as cell signaling, DNA repair, gene control, cell death, and response to stress. Recently, a group of neurological disorders due to ADPRHL2 variants is described, characterized by childhood-onset, stress-induced variable movement disorders, neuropathy, seizures, and neurodegenerative course. We present the diagnostic pathway of two pediatric patients with episodic dystonia and ataxia, who later had a neurodegenerative course complicated by central hypoventilation syndrome due to the same homozygous ADPRHL2 variant. We conducted a systematic literature search and data extraction procedure following the Preferred Reporting Items for Systematic Review and Meta-Analysis 2020 statement in terms of patients with ADPRHL2 variants, from 2018 up to 3 February, 2023. In total, 12 articles describing 47 patients were included in the final analysis. Median age at symptom onset was 2 (0.7–25) years, with the most common presenting symptoms being gait problems (n = 19, 40.4%), seizures (n = 16, 34%), ataxia (n = 13, 27.6%), and weakness (n = 10, 21.2%). Triggering factors (28/47; 59.5%) and regression (28/43; 60.4%), axonal polyneuropathy (9/23; 39.1%), and cerebral and cerebellar atrophy with white matter changes (28/36; 77.7%) were the other clues. The fatality rate and median age of death were 44.6% (n = 21) and 7 (2–34) years, respectively. ADPRHL2 variants should be considered in the context of episodic, stress-induced pediatric and adult-onset movement disorders and seizures.
Keywords: ADPRHL2; episodic ataxia; dystonia; dyskinesia; central hypoventilation